Techniques in the treatment of sense in the translation of English and Chinese hymns / Rebecca Mccort - Rebecca , Mccort (2024)
This study aims to identify and compare the use of translation techniques from existing taxonomies that prevail in the treatment of sense in English-Chinese (En-Ch) and Chinese-English (Ch-En) hymn translation, and to descriptively identify any additional novel translation techniques that prevail in the selected hymn set. Twenty pairs of ST and TT hymns were selected from The New Hymnal: English-Chinese bilingual edition (1999). Of these, ten pairs were En-Ch translations, and ten were Ch-En. Source text (ST) and target text (TT) hymn lyrics were analyzed to identify use of Low’s (2017) song lyric translation techniques, as well as techniques for written translation proposed by Vinay & Darbelnet (1995), Baker (1992), and Newmark (1988). Novel translation techniques not included in any of these taxonomies were identified through descriptive analysis. Results revealed that Dilution, Modulation, Near-synonym, Compensation, and Transposition are the five most commonly used translation techniques for En-Ch translations, whereas Dilution, Near-synonym, Changing the kind of utterance, Modulation, and Compensation are the five most used techniques for Ch-En translations. Novel techniques identified in En-Ch translations include Partial transfer, More descriptive term, Change to figure of speech, Intra-line position change, and Pronoun change. Novel techniques in Ch-En translations include Partial transfer, Intra-line position change, Change to figure of speech, Pronoun change, Statement to address, and Phrase to sentence. Though failing to qualify as translation techniques, Addition and Replacement also play a significant role in both directions of translation. Findings emphasize the suitability of Low’s (2017) techniques for song translation and suggest which techniques from this song-translation-specific taxonomy are most useful in producing successful song translations. The research also highlights the range of techniques translators draw on for flexible handling of semantics, revealing the intentional and artful nature of song translation.